Cold gas spray coatings: basic principles corrosion protection and applications - Silva, Fernando Santos da; Cinca, Núria; Dosta, Sergi; Cano, Irene Garcia; Guilemany, Josep Maria; Benedetti, Assis Vicente (Eclética Química, 2017)
In this review, the beginnings and evolution of the cold gas spray (CGS) technique are described, followed by the main fundamental aspects of the technique together with a description of the several spraying systems up to date. Sequentially, the main spray parameters and their influence on the properties of the coatings are reported. Afterwards, the most important methodologies for preparing the feedstock powders to be sprayed, the effect of the powder composition, microstructure, particle size and shape on the properties of the coatings are discussed. The nature of the spray gun and nozzle, and the substrate pre-treatments were also discussed. With regard to microstructure and properties, the chemical and physical characterization of the coatings and the performance in protecting the substrates against corrosion together with some mechanical properties are presented and compared. The lacking systematic studies about the great part of investigated systems is the main drawback to compare the published results. Closing this review, the main applications, and the potentialities of the CGS coatings are evidenced.